Analisis Ekonomi Islam terhadap Distorsi Ekonomi dalam Transaksi Sekuritas pada Pasar Sekunder - Fitrah Maharaja (Universitas Batanghari Jambi, 2022)
The purpose of this study is to find out from the results of previous studies regarding market distortions in the process of securities transactions according to Islamic Economics in the secondary market. In this study using descriptive qualitative methods where the authors conducted this study using descriptive data in the form of words or literature reviews from previous studies. The data collection used by the author in this study is the publication of previous scientific journals related to the influence of foreign debt by the Indonesian state. The results of this study found that Islamic Economics requires a free market mechanism without any intervention. Fair and fair prices come from prices obtained based on the power of supply and demand. Islamic economics emphasizes that market mechanisms and price fixing need to be regulated to uphold market balance and economic justice by considering the interests of the parties involved in the market. Market distortion is a form of deviation that causes imbalances and injustices in the market which must be regulated by the government through intervention policies under its authority.